Mathematical Creative Thinking Ability for Students Through REACT Strategies - Qadri, Lailatul; Ikhsan, M.; Yusrizal, Yusrizal (International Journal for Educational and Vocational Studies, 2019)
The ability to think creatively is important to create students who can use mathematical mindset in their daily activities, and in various sciences. The conditions at school this time show us that students still run into problems in resolve math questions which related to mathematical creative thinking ability that finally impact on the result is low for this ability. Therefore, we need strategy for mathematics learning so it can improve  mathematical creative thinking ability for students. The strategy that can be applied are through Relating, Experiencing, Applying, Cooperating, dan Transferring (REACT). This research aims to know the improvement creative thinking mathematical ability for students through react strategy. The type of this research is experimental research with a quantitative approach. The populations in this study are students in class X SMAN 1 Banda Aceh. The sample in this study is students in class X MIA-3 as an experimental class that gets learning with REACT’s strategy, and students in class X MIA-1 as a control class that has conventional learning. The instrument of this research is the questions of pretest and post-test. The quantitative analysis using a test independent sample t-test. Based on the results of data analysis it can be concluded that improvement creative thinking mathematical ability for students by teaching with REACT’s strategy is better than improvement of students' creative thinking skills by teaching conventionally.